2021
DOI: 10.14430/arctic73773
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing the Power of Community Science to Address Data Gaps in Arctic Observing: Invasive Species in Alaska as Case Examples

Abstract: The Arctic is undergoing large-scale changes that are likely to accelerate in future decades such as introductions and expansions of invasive species. The Arctic is in a unique position to prevent new introductions and spread of existing invasive species by adopting policies and actions aimed at early detection. Responding to threats from invasive species to minimize impacts to ecosystems, communities, food security, and northern economies will necessitate extensive observations and monitoring, but resource ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Resource managers operating at global invasion fronts such as found in Arctic wilderness areas often face decisions requiring rapid response to avoid ecosystem damages but lack adequate information to support their decisions (Liu et al 2012). Invasion management is particularly challenging for aquatic invasive species transmitted via aircraft because detection and ultimately treatment in remote waterbodies is difficult (Schwoerer et al 2021). In this study, we showed that using a survey with human operators of mechanical invasive species vectors-in this case floatplane pilots and their flight patterns-can be used for predictive modeling to inform early detection, an approach suitable for other data-limited situations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resource managers operating at global invasion fronts such as found in Arctic wilderness areas often face decisions requiring rapid response to avoid ecosystem damages but lack adequate information to support their decisions (Liu et al 2012). Invasion management is particularly challenging for aquatic invasive species transmitted via aircraft because detection and ultimately treatment in remote waterbodies is difficult (Schwoerer et al 2021). In this study, we showed that using a survey with human operators of mechanical invasive species vectors-in this case floatplane pilots and their flight patterns-can be used for predictive modeling to inform early detection, an approach suitable for other data-limited situations.…”
Section: Discussionmentioning
confidence: 99%
“…This data scarcity is most symptomatic where large tracts of natural environment remain (Gaulke et al 2019). Remoteness and the associated high cost of monitoring and data collection can lead to additional management challenges (Schwoerer et al 2021). These management challenges are exacerbated when the invader is difficult to detect and thus more likely to be established before detection, as is often the case with aquatic invasive species (AIS) (Sytsma and Pennington 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In the far north, where climate change is accelerating faster than the rest of the world [15], CCS is an important tool to monitor and respond to local climate change impacts [16,17]. There are important roles for both contributory and co-created CCS projects to play: contributory projects can be deployed rapidly and gather large amounts of information across the vast and remote northern geography, while co-created projects allow for deep engagement with local issues in specific communities [18]. Co-creation approaches to developing projects, which can be the start of co-production of knowledge between two different knowledge systems, center equitable distribution of power between Indigenous communities and Western scientists, and are increasingly visible and emphasized in Arctic sciences [19,20].…”
Section: Equity In Community and Citizen Science Designmentioning
confidence: 99%
“…We measured youths' science self-efficacy and science interest using five-item Likert scales adapted from the DEVISE (Developing, Validating, and Implementing Situated Evaluation Instruments) project, created and validated by the Cornell Lab of Ornithology [44,45]. The other survey items were developed by co-author K. Spellman and program evaluator A. Larson based on a literature review of citizen science program quality indicators [18,46], and these items are not used in this study. All statistical analyses were conducted in R Studio.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…These species were introduced through ornamental trade and have been dispersed by several vectors, such as seaplanes, in the more remote areas. Seaplane pilots were involved in the collection of data on flight destinations and annual flight frequencies using an electronic mapping tool (Schwoerer et al, 2022). These data were used to model introduction pathways, show the economic cost of unintentionally carrying Elodea spp.…”
Section: Monitoring Invasions By Alien Speciesmentioning
confidence: 99%